1994
DOI: 10.1128/jb.176.17.5560-5564.1994
|View full text |Cite
|
Sign up to set email alerts
|

Growth rate-dependent control of the rrnB P1 core promoter in Escherichia coli

Abstract: We have extended our previous studies of the DNA sequences required for growth rate-dependent control of rRNA transcription in Escherichia coli. Utilizing a reporter system suitable for evaluation of promoters with low activities, we have found that the core promoter region of mnB P1 (-41 to + 1 with respect to the transcription initiation site) is sufficient for growth rate-dependent control of transcription, both in the presence and in the absence of guanosine 3'-diphosphate 5'-diphosphate (ppGpp). The core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
1
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(75 citation statements)
references
References 33 publications
6
67
1
1
Order By: Relevance
“…Although UP elements and Fis sites are required for maximal strength, rrn P1 promoters lacking these sequences (core promoters) are still regulated in response to the cell's nutritional environment (9,10). Consistent with this finding, cells lacking the fis gene regulate transcription from rrn P1 promoters similarly to wild-type strains, because feedback systems compensate for the loss of Fis (7).…”
supporting
confidence: 72%
See 2 more Smart Citations
“…Although UP elements and Fis sites are required for maximal strength, rrn P1 promoters lacking these sequences (core promoters) are still regulated in response to the cell's nutritional environment (9,10). Consistent with this finding, cells lacking the fis gene regulate transcription from rrn P1 promoters similarly to wild-type strains, because feedback systems compensate for the loss of Fis (7).…”
supporting
confidence: 72%
“…ppGpp shortens the half-lives of open complexes formed at all promoters, but it only inhibits transcription from those promoters (such as rrn P1) where this step is rate-limiting (11). Strains that cannot make ppGpp exhibit relatively normal rRNA transcription during steady-state growth, in contrast to the situation during a stringent response (9,11,14).The short half-life of rrn P1 open complexes also results in a requirement in vitro for concentrations of initiating nucleoside triphosphates that are much higher than for other promoters (15). Consistent with this observation, when purine NTP concentrations are elevated in vivo by limitation for pyrimidines, rrnB P1 promoter activity increases in parallel with the ATP concentration (15).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This contrasts with the situation at two other growth rate-regulated promoters (rrnB P1 and the leuV promoter), where GRDC does not require the UP element (2,3,29). Our results also show that, in addition to the P guaB UP element, sequences located between positions Ϫ133 and Ϫ100 are required for GRDC, and their role is to facilitate the inhibition of P guaB at lower growth rates.…”
Section: Vol 190 2008contrasting
confidence: 39%
“…Consistent with this, it has been shown that P guaB activity is subject to GRDC (8). The bestcharacterized promoter subject to GRDC that also contains an UP element is the rrnB P1 promoter, although the UP element plays no role in GRDC of this promoter (2,28). In this work, we show that the AϩT-rich sequence located upstream of the P guaB Ϫ35 region does indeed function as an UP element and that, like the rrnB P1 UP element, it contains promoter-proximal and -distal subsites that are able to activate transcription…”
mentioning
confidence: 74%